Fast-Growing Trees Species-Opportunities and Risks for Sustainable Agricultural and Forest Land Use Systems - Landgraf, Dirk (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The articles in this Special Issue cover a very wide range of topics related to the cultivation, management and use of fast-growing tree species. In addition to research on breeding and on the influence of pruning practices on the height growth of paulownia, three articles deal with the influence of site characteristics and nutrient availability on the physiology and yield security of fast-growing tree species. Another article focuses on the modeling of soil carbon in Salix plantations, while the article by Boruszewski et al. reports on potentially suitable areas for the planting of fast-growing tree species in Poland. Zitzmann and Rode examine the impact of short-rotation plantation management on phytodiversity, while Helbig et al. deal with the influence of leaf feeding on the growth of poplars and willows. Finally, Hernandez-Estrada et al. describe the dry matter loss of poplar wood chips during storage.